Redistributing Equity: A Contemporary Analysis of Justice in Islamic Economic Thought - Lina Elpina (Jurnal Iman dan Spiritualitas, 2026)
Islam has a universal concept of a system of life and forms a complete order to regulate human life. As a guideline for life, Islam regulates various social, educational, and economic aspects. Islam has formulated an economic system based on sharia. Many economic problems can lead to social inequality. This inequality begins with an economic system that lacks a just perspective. Therefore, in this case, the researcher is interested in comprehensively examining the concept of justice from an Islamic economic perspective. This research utilizes literature from books, articles, and other sources related to the research theme. The results of the study indicate that justice from a Sharia economic perspective can be understood as economic activities carried out fairly by economic actors and without acts of oppression against others. Islam views justice as an obligatory and absolute provision as a crucial element in social and humanitarian life. Justice is a provision mandated by Allah SWT for all people in the world without exception.